2021
DOI: 10.1021/acs.nanolett.1c02237
|View full text |Cite
|
Sign up to set email alerts
|

Squeeze-Film Effect on Atomically Thin Resonators in the High-Pressure Limit

Abstract: The resonance frequency of membranes depends on the gas pressure due to the squeeze-film effect, induced by the compression of a thin gas film that is trapped underneath the resonator by the high-frequency motion. This effect is particularly large in low-mass graphene membranes, which makes them promising candidates for pressure-sensing applications. Here, we study the squeeze-film effect in single-layer graphene resonators and find that their resonance frequency is lower than expected from models assuming ide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In addition, the airflow during the pressure decrease process in the chamber may affect the resonant frequency of the resonator because of gas leakage from the sealed cavity. In the ultrahigh-vacuum region (pressures lower than 5 × 10 –4 mbar) the squeeze damping effect , might also play a role. Furthermore, the thermal conductivity of the ambient air decreases as the pressure decreases, such that the temperature of the graphene membrane increases.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the airflow during the pressure decrease process in the chamber may affect the resonant frequency of the resonator because of gas leakage from the sealed cavity. In the ultrahigh-vacuum region (pressures lower than 5 × 10 –4 mbar) the squeeze damping effect , might also play a role. Furthermore, the thermal conductivity of the ambient air decreases as the pressure decreases, such that the temperature of the graphene membrane increases.…”
Section: Resultsmentioning
confidence: 99%
“…Also, graphene has an ultrahigh thermal conductivity , and fatigue life, which combined with its high Young’s modulus, , low mass density, , and large surface area make graphene a strong candidate for resonant sensors . Since the first realization of graphene mechanical resonators by Bunch et al, many experimental , and theoretical studies have shown that graphene resonators promise to be ultrasensitive detectors of force, mass, and charge …”
Section: Introductionmentioning
confidence: 99%
“…Along with this comes a massively reduced effective mass, increased resonance frequencies, easily accessible non-linearity, and the ability to tune resonance frequencies [9]. This technological boost allows using such resonators as sensors for light [10], magnetic fields [11,12], sound [6,[13][14][15], gases [6,16] or even to study live bacteria [17].…”
Section: Introductionmentioning
confidence: 99%